The Potency of Corn (Zea Mays) Cob Waste as a Prebiotic Candidate to Support the Growth of Bifidobacterium longum: a Preliminary Study - Aprilia Ariestanti, Catarina; Ananda Sejati1, Ribka; Thea Setyaratri, Fransiska; Angel Meliana, Florencia (Universitas Kristen Duta Wacana, 2022)
Corn cob is one of the most common agricultural wastes in Indonesia with high content of xylan. Xylan can be used to produce xylitol which cannot be digested by human digestive enzymes thus, make it a potential candidate of prebiotic. This preliminary research aimed to study the potency of corn cob in supporting the growth of Bifidobacterium longum. Corn cob was produced into powder and used as the carbon source in the growth medium of B. longum. Total plate count method was done to count the growth of B. longum in various concentrations of bacteria solution. The result showed that crude corn cob powder can support the growth of B. longum from bacterial enumeration with the value of 2.01 x 106 CFU/mL. The study indicated that corn cob has a potential to be used as prebiotic.